86.0k views
3 votes
5x + 2 = 3x + 4(2x - 1) please solve step by step

2 Answers

5 votes
your answer is x=1 (i think)
User Ortwin Angermeier
by
5.5k points
7 votes

Answer:

x=1

Explanation:

Step 1: Simplify both sides of the equation.

5x+2=3x+4(2x−1)

5x+2=3x+(4)(2x)+(4)(−1)(Distribute)

5x+2=3x+8x+−4

5x+2=(3x+8x)+(−4)(Combine Like Terms)

5x+2=11x+−4

5x+2=11x−4

Step 2: Subtract 11x from both sides.

5x+2−11x=11x−4−11x

−6x+2=−4

Step 3: Subtract 2 from both sides.

−6x+2−2=−4−2

−6x=−6

Step 4: Divide both sides by -6.

−6x

−6

=

−6

−6

x=1

Answer:

x=1

User Perrako
by
4.6k points